Toward sustainable school building design: a case study in hot and humid climate - Alwetaishi, M.; Gadi, Mohamed (Cogent OA, 2018)
There is a global concern about energy in buildings generally for two major reasons. The first one is to minimise the energy consumption in buildings, while the other is to provide thermally comfortable buildings with minimum energy usage. Most of the work carried out in buildings was in office as well as domestic sector. However, the limited publication was done in educational buildings generally. The significance of this research is to take into consideration the energy pattern in a school building in the Kingdom of Saudi Arabia. The research is going to use TAS EDSL computer modelling with its validation. TAS is one of the most commonly used software globally to predict energy building performance. In addition to that, the school will be visited for monitoring. Several types of advanced tools will be used to measure indoor air temperature, relative humidity and much more. This investigation shows that the utilisation of natural ventilation has a major impact on internal temperatures. It has lowered the minimum by 6°C and also lowered the maximum by 3°C. In addition to that, there is a noticeable influence on the top classroom which has its roof exposed to the outdoors. Such outcomes can serve the new vision of Saudi Arabia 2030 and aid to improve the reliance of its buildings on energy.